O Almirante Tamandaré através da Revista Marítima Brasileira: a construção da memória de uma instituição da Marinha do Brasil (1897-1950) - Paulo André Leira Parenteme de Andréa Frota (Navigator)
This article shows the memory construction process of Admiral Tamandaré as an institution of the Brazilian Navy by way of the magazine Revista Marítima Brasileira, between the years 1897 and 1950. In this period, which ranges from the moment of his passing up until the institutionalization of his memory, we have identified three distinct phases: first, the moment immediately surrounding his passing, in 1897, when he was pronounced a hero; then, a second phase ranging from 1897 to 1932, wherein he was all but forgotten by the editors of the magazine; and finally, a third phase wherein, by way of a fight to revive his memory, he became a hero of Brazilian history and an institution in the Brazilian Navy.